2018
DOI: 10.1016/j.bjan.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

O bloqueio do plano transverso abdominal subcostal pode melhorar a analgesia após colecistectomia laparoscópica

Abstract: Our results show that subcostal transversus abdominis plane block can provide superior postoperative analgesia and reduction in opioid requirements after laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…16 Similar finding was reported by V.Vrsajkov et al (p<0.01). 21 In our study we found that differences in 24 hours VAS score was statistically significant. In study conducted by Suseela et al 22 with sample size of 40 in each group found ultrasound guided Subcostal TAP block is superior to port-site infiltration in providing post-operative analgesia after laparoscopic cholecystectomy with reduced pain scores(p<0.001) which is consistent with our study.…”
Section: Discussionsupporting
confidence: 50%
“…16 Similar finding was reported by V.Vrsajkov et al (p<0.01). 21 In our study we found that differences in 24 hours VAS score was statistically significant. In study conducted by Suseela et al 22 with sample size of 40 in each group found ultrasound guided Subcostal TAP block is superior to port-site infiltration in providing post-operative analgesia after laparoscopic cholecystectomy with reduced pain scores(p<0.001) which is consistent with our study.…”
Section: Discussionsupporting
confidence: 50%
“…In total, 22 of the included studies compared pre-operative TAP block with a control [ 22 , 23 , 25 , 27 29 , 31 , 33 , 35 43 , 45 , 46 , 49 , 52 , 54 ], 11 evaluated the effect of postoperative TAP block compared with a control block [ 24 , 26 , 30 , 32 , 34 , 44 , 47 , 48 , 50 , 51 , 53 ], and only one directly compared pre-operative TAP block with postoperative TAP block [ 11 ]. A total of 2317 patients were enrolled in the included trials: 456 patients were randomised to the postoperative TAP block group, 773 to the pre-operative TAP block group, and the remaining to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…For the primary outcome of pain control at rest and during coughing, out of 23 studies, 22 studies were included in the analysis for which references have been provided in Table 3 . Some of the included studies had reported data only for one or two timepoints for post-operative pain score either for 0 or 6 or 12 or 24 h at rest or during coughing ( 17 , 18 , 20 , 22 24 , 26 , 28 , 30 , 36 38 ). A single study by El-Dawlatly et al ( 27 ) only provided the data for morphine consumption.…”
Section: Resultsmentioning
confidence: 99%
“…A single study by El-Dawlatly et al ( 27 ) only provided the data for morphine consumption. PONV data was available for 12 studies ( 16 , 18 , 19 , 21 , 23 , 25 , 28 , 29 , 31 , 33 , 36 , 37 ) (750 LC patients). Information on morphine consumption up to 24 h post-operation was reported by seven studies ( 16 , 17 , 23 , 27 – 29 , 31 ) (348 LC subjects).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation